Planning and Implementation of Educational Institutions at the LKP Nida Course - Ayuning, Riska; Rahayu, Rismawati; Wijayanto, Wasis (Journal of Nonformal Education and Community Empowerment, 2024)
This research aims to narrative the planning and implementation at LKP Nida Course Kudus. This research uses a qualitative approach, the research subject is one person who owns the LKP Nida Course. Data collection techniques used were observation, interviews and documentation. For data validity, technical triangulation and source triangulation are used. Data analysis techniques with stages of data collection, data reduction, data presentation, and drawing conclusions. Where LKP Nida Course has its own administration for profits, asset improvements, employee salaries and so on. The results of the research show that management at LKP Nida Course is related to planning, training objectives, learning media, management which has been running well for 7 years.